PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK), DAN DANA BAGI HASIL (DBH) TERHADAP BELANJA MODAL (Studi Kasus Kabupaten/Kota di Indonesia Tahun 2016) - Zahrotun Nisa; Ronny Malavia Mardani; Muhammad Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis study aims to determine the effect of Locally generated, GeneralAllocation Funds, Special Allocation Funds, and Revenue Sharing Funds toCapital Expenditures in Districts / Cities in Indonesia in 2016.This research is a comparative causal research. The data of research onincoming region (PAD), Generally for Allocation Fund (DAU), Specifically forAllocation Fund (DAK) and Profit Sharing Fund (DBH) to Capital Expenditurederived from realization report of APBD districts and cities Indonesia in 2016,obtained from official site Directorate General of Fiscal Balance. The populationin this study is all districts and municipalities in Indonesia in 2016 with theexception of Tebing Tinggi city, Bukit Tinggi, regency of Lampung Timur andSukoharjo with the number of districts and cities that is 508.Technique datacollection using documentation method. The data analysis using normality test,classical assumption test, multiple linear regression ,and hypothesis test.Based on the result of research can be concluded that partially variableof PAD and DAU there is no significant influence to capital expenditure. While,DAK and DBH variables have significant influence to capital expenditure.Keywords : Locally Generated Revenue, Generally Allocation Fund, SpecificallyAllocation Fund and Profit Sharing Fund, Capital Expenditure.